New insights into the mechanisms behind mechanical itch. Issue 8 (19th July 2020) - Sakai, Kent; Akiyama, Tasuku
Abstract: Gentle tactile stimuli, such as insects crawling on the skin, can cause itching sensation called mechanical itch. Recent studies have begun to shed light on the neural mechanisms of mechanical itch. Interestingly, the neural pathway for mechanical itch is apparently different from that for chemical itch triggered by the activation of pruriceptors with various mediators. Mechanical itch dysesthesia is frequently seen in patients with chronic itch. Mechanisms of this dysesthesia are plausibly involved in central sensitization. In this review, we summarize the current knowledge of mechanical itch under normal and pathological conditions.